2020
DOI: 10.1021/acs.jmedchem.0c00369
|View full text |Cite
|
Sign up to set email alerts
|

Damage Incorporated: Discovery of the Potent, Highly Selective, Orally Available ATR Inhibitor BAY 1895344 with Favorable Pharmacokinetic Properties and Promising Efficacy in Monotherapy and in Combination Treatments in Preclinical Tumor Models

Abstract: The ATR kinase plays a key role in the DNA damage response by activating essential signaling pathways of DNA damage repair, especially in response to replication stress. Because DNA damage and replication stress are major sources of genomic instability, selective ATR inhibition has been recognized as a promising new approach in cancer therapy. We now report the identification and preclinical evaluation of the novel, clinical ATR inhibitor BAY 1895344. Starting from quinoline 2 with weak ATR inhibitory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…ATR inhibitors, such as AZD6738 and VE-821 as well as the CHK1 inhibitor SAR-020106 were effective radiosensitizers in preclinical studies (100)(101)(102). An ongoing phase I clinical trial (NCT03188965) is assessing the safety profile of ATR inhibitors (BAY1895344) (103).…”
Section: Atr-chk1mentioning
confidence: 99%
“…ATR inhibitors, such as AZD6738 and VE-821 as well as the CHK1 inhibitor SAR-020106 were effective radiosensitizers in preclinical studies (100)(101)(102). An ongoing phase I clinical trial (NCT03188965) is assessing the safety profile of ATR inhibitors (BAY1895344) (103).…”
Section: Atr-chk1mentioning
confidence: 99%
“…Following these initial studies, several structurally unrelated ATR inhibitors have been described and widely assayed in multiple preclinical models of cancers [ 91 , 92 , 93 , 94 , 95 , 96 ]. Recently, phase I/II cancer clinical trials have been launched to assess the role of ATR inhibitors, either as single agents or in combinations with chemotherapy, radiotherapy, and immunotherapy in patients with advanced and refractory solid tumors (clinicaltrials.gov and [ 97 ]), with the first results reported [ 98 , 99 , 100 , 101 ].…”
Section: Harnessing Replicative Stress As a Cancer Vulnerability In MMmentioning
confidence: 99%
“…BAY 1895344 is another oral selective and potent ATR inhibitor discovered and optimized for in vivo studies using the high-throughput screening of chemical compounds [61]. Preclinical studies of this drug as monotherapy in DDR deficiencies revealed promising antitumor activity as well as synergistic activity in combination with DNA damage-inducing chemotherapy or radiotherapy [62].…”
Section: Atr Inhibitorsmentioning
confidence: 99%